Export av får och nötkreatur från Australien - Björkman, Mikaela (2010)
Live exports of animals began during the late 19th century and are nowadays a valuable alternative to the slaughter industry in Australia. About four million sheep and half a million to one million cattle are exported annually from Australia to the Middle East and Southeast Asia. Most of these animals are exported for slaughter, but some cattle are exported with the purpose of breeding. One factor that has been the driving force for the live export industry is that countries through tariffs and other barriers have favored the import of live animals rather than the import of meat.